Optimalisasi durasi pemberian ASI dengan pertumbuhan berat badan bayi usia 7-12 bulan - Aryanti Wardiyah; Rahma Elliya; Muhammad Johan Bastomi (Holistik Jurnal Kesehatan, 2021)
The optimization duration of exclusive breastfeeding and physical growth of infants 7 to 12 months of age Background: Breastfeeding will keep the baby healthy and starts life in the healthiest way, breast milk has an important role in maintaining the health and survive, because babies who are exclusively breastfed have a better immune system than babies who are not breastfed. Based on data obtained at the Rejo Katon Health Center, the coverage of exclusive breastfeeding in 2016 was 46.2%, in 2017 it was 34.6% and in 2018 it was 30.4%, it is known that the difference in body weight of infants who receive exclusive breastfeeding and formula milk in Rejo Katon Health Center Work Area in 2020.Purpose: To determine The relationship between baby weight and the optimal duration of exclusive breastfeedingMethod: This type of quantitative analytic research with a case control approach, the subjects in this study were all babies in the working area of Rejo Katon Health Center. The variables in the study were infant weight, exclusive breastfeeding, and formula milk. The research was conducted in July 2020, in the working area of the Rejo Katon Community Health Center.Results: It is known that there are 50 (50.0%) infants who are exclusively breastfed, 58 (58.0%) babies with normal weight. There is a difference in the body weight of infants who receive exclusive breastfeeding and the body weight of infants who receive formula milk in Rejo Katon Health Center Work Area in 2020 p-value 0.026 and OR 2.7.Conclusion: There are differences in body weight of infants who receive exclusive breastfeeding and the weight of babies who receive formula milk in the Work Area of the Rejo Katon Health Center in 2020. Suggestions for mothers to be able to provide good nutrition to their children. Pay attention to the child's weight by monitoring and paying attention to the nutrition consumedKeywords: Exclusive breastfeeding; Physical growth; InfantsPendahuluan: Menyusui akan menjamin bayi tetap sehat dan memulai kehidupannya  dengan cara yang paling sehat, ASI memiliki peranan penting dalam menjaga kesehatan dan  kelangsungan hidup bayi, karena bayi yang diberi ASI secara eksklusif memiliki daya tahan  tubuh yang lebih baik dibandingkan bayi yang tidak diberikan ASI eksklusif, Berdasarkan  data yang diperoleh di Puskesmas Rejo Katon cakupan ASI eksklusif tahun 2016 sebesar  46,2%, tahun 2017 sebesar 34,6% dan tahun 2018 sebesar 30,4%, diketahui perbedaan berat  badan bayi yang mendapatkan ASI eksklusif dan tidak ASI eksklusif di Wilayah Kerja  Puskesmas Rejo Katon Tahun 2020.  Tujuan: untuk mengetahui Optimalisasi durasi pemberian ASI dengan pertumbuhan berat badan bayi usia 7-12 bulan.Metode: Jenis penelitian analitik kuantitatif dengan pendekatan case control,  subjek dalam penelitian ini adalah seluruh bayi yang ada di wilayah kerja Puskesmas Rejo  Katon. Variabel dalam penelitian adalah berat badan bayi, ASI eksklusif, dan tidak ASI  eksklusif . Penelitian telah dilaksanakan pada bulan Juli 2020, di wilayah kerja Puskesmas  Rejo Katon.  Hasil : Diketahui bayi yang diberikan ASI eksklusif sebanyak 50 (50,0%) bayi, bayi dengan  berat badan normal sebanyak 58 (58,0%) , Ada perbedaan berat badan bayi yang  mendapatkan ASI eksklusif dengan berat badan bayi yang mendapatkan tidak ASI eksklusif  di Wilayah Kerja Puskesmas Rejo Katon Tahun 2020 p-value 0,026 dan OR 2,7.  Simpulan : Ada perbedaan berat badan bayi yang mendapatkan ASI eksklusif dengan  berat badan bayi yang mendapatkan tidak ASI eksklusif di Wilayah Kerja Puskesmas Rejo  Katon Tahun 2020. Saran bagi ibu untuk dapat memberikan nutrisi yang baik pada anaknya.  Memperhatikan berat badan anaknya dengan melakukan pemantauan dan perhatian pada gizi  yang dikonsumsi